Factors influencing the effectiveness of clinical learning environment in nursing education - Elena Gurková; Katarína Žiaková; Silvia Cibríková; Dagmar Magurová; Anna Hudáková; Slávka Mrosková (University of Ostrava, 2016)
Aim: The purpose of the cross-sectional descriptive study was to investigate how nursing students evaluate particular factors of clinical learning environment during their professional placement in hospitals. We explored which factors of clinical environment contribute significantly to students' evaluation of it. Design: A descriptive cross-sectional study. Methods: The sample included 503 nursing students in their second or third year of study at six Slovak universities. A valid and reliable questionnaire, the Clinical Learning Environment, Supervision and Nurse Teacher evaluation scale (CLES+T), was used to evaluate the student nurses' experiences and clinical placement. The data were analysed using descriptive statistics, Pearson's chi-square test, multifactorial ANOVA procedure and Pearsons' correlations, and p-value < 0.05 was taken to indicate statistical significance for all comparisons. Results: A significant proportion of students experienced a traditional model of group supervision. Supervision method, supervisory session frequency, and duration of clinical placement had a significant impact on their evaluation of clinical environments. Conclusion: Supervision methods are a significant factor influencing student evaluation of their clinical placement environment. Compared to other European studies, we found a less frequent application of individual supervision and that the Slovak university setting is dominated by a traditional group model of supervision. The study offers a valuable insight into the analysis of factors contributing to improvements in clinical learning environment and models of clinical or workplace training.